The Influence of Tackifier Concentration on Acrylic Pressure Sensitive Adhesives - Monir Shalbafan; H. Bayati; Ebrahim Hashemi (Orbital: The Electronic Journal of Chemistry)
Different combinations of tackifiers were used to create a series of pressure-sensitive adhesives (PSAs) in order to find the optimal balance between peel resistance, tack, and shear resistance. The goal of the study was to analyze how varying levels of tackifier content, specifically rosin ester (RS), impact the key characteristics of an acrylic PSA, such as tack, peel, and shear strength. The addition of rosin ester tackifiers to acrylic PSAs was found to increase the viscosity of the adhesive due to the surface-active nature of the tackifiers. As the concentration of tackifier increased, the number of micelle particles in the solution also increased, leading to higher viscosity and particle size. Increasing the tackifier concentration saturated the active space in the adhesive structure, resulting in the formation of smaller and weaker polymers. This change in the polymerization process led to a decrease in Tack and Peel strength. The study indicated that RS showed the highest compatibility with the synthesized PSA. Interestingly, the inclusion of 2 wt % of RS caused significant changes in the tack and peel properties of the PSA, but it also led to a notable decrease in shear strength.